Effect of drying on flavour quality of Indian spearmint (Mentha spicata L.) - RAO, M L SHANKARANARAYANA, B RAGHAVAN, K O ABRAHAM, L JAGANMOHAN (Journal of Spices and Aromatic Crops, 1994)
The essential oils obtained from Indian spearmint (Mentha spicata L.) subjected to different drying procedures were analysed employing gas chromatography and gas chromatography-mass spectrometry techniques. Forty three flavour components were identified, of which eucarvone, cubenol and a-cadinol are reported for the first time. The essential oil had a higher percentage of limonene (26.82%) compared to Italian and American oils. Carvone to limonene ratios were 2.2:1.0 and 2.3:1.0 in the oil from fresh and shade-dried spearmint, respectively. Blanching leaves prior to drying yielded products which were unattractive with respect to colour and appearance and were also bland and odourless due to loss of volatile oil during drying. Storing fresh leaves for 12 h after spraying with water increased the volatile oil content by about 6%. Shade drying leaves resulted in a product with a good green colour and minimum loss of volatile oil compared to other drying methods.